Researching the dyslipidemia treatment effect of Ha mo NK total extract in experiment - Pham, Thuy Phuong; Hoang, Trong Quan; Nguyen, Pham Ngoc Mai; Nguyen, Thanh Luan; Trinh, Vu Lam; Le, Minh Trung (Tạp chí Y Dược cổ truyền Việt Nam, 2025)
Objective: To study the acute toxicity and dyslipidemia treatment effects of Ha mo NK total extracts in experiment. Subjects and methods: Study the acute toxicity on Swiss albino, both genders, weighing 18 - 22g. Study the dyslipidemia treatment effects on Swiss albino, both genders, weighing 25 ± 2g using empirical endogenous model. Results: The LD50 of Ha mo NK total extract has not been determined, there were no signs of acute toxicity at a dose of 59.52 grams of Ha mo NK/kg (12,33 times higher than the expected clinical dose). The Ha mo NK total extract at a dose of 4.8g/kg/day (equivalent to the expected clinical dose) and 14.5g total extract/kg/day has the effect of reducing the concentration of total cholesterol and non-HDL-Cholesterol with total cholesterol reduction levels of 20.4% and 18.1% respectively compared to the model batch, the difference is significant statistics at p<0.01, tends to increase HDL-Cholesterol concentration, and reduce Triglyceride in white mice modeled with P-407-induced dyslipidemia. Conclusion: The total extract Ha mo NK at a dose 12.33 times higher than the expected human dose but has no acute toxicity in mice, orally. The total extract of Ha mo NK at a dose of 4.8g/kg/day (equivalent to the expected clinical dose) and 14.5g/kg/day (3 times the expected clinical dose on humans) tended to increase HDL-Cholesterol index, and reduce Triglyceride; and had the effect of reducing total cholesterol (TC) and non-HDL-Cholesterol index in white mice modeled with dyslipidemia by P-407.